Perceraian Akibat Kekerasan Dalam Rumah Tangga di Pengadilan Agama Gorontalo - Fauzia Latief; Mutia CH. Thalib; Suwitno Yutye Imran (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine and analyze empirical juridical analysis of divorce due to domestic violence in the Gorontalo Religious Court and the factors causing divorce due to domestic violence in the Gorontalo Religious Court. This research discusses problems regarding divorce due to domestic violence in the Gorontalo Religious Court. This type of research is empirical juridical research or what is called field research. The results of this research explain that the empirical juridical analysis of divorce in the Gorontalo Religious Courts is caused by domestic violence, especially violence against wives, caused by various problems that are interrelated and influence each other, causing continuous disputes and quarrels. These problems include: economic conditions, lack of understanding of religion, infidelity, jealousy, drunkenness and gambling, husbands are easily emotional and are caused by the presence of one of the parents on both sides taking part in the household which can lead to a household crisis. In this case, the wife becomes vulnerable to violence because of her unequal position in society and the institution of marriage, both emotionally, socially and emotionally. This research shows that domestic violence is a significant factor in triggering divorce cases filed in the Religious Courts. And the factors that cause divorce due to domestic violence in the Gorontalo Religious Court are the dominant factors that cause divorce due to domestic violence, namely: that there is a lack of religious understanding, behavioral factors, social factors, drunkards and gamblers, disputes or quarrels and other factors. domestic violence.